The Christchurch prisons psychiatric epidemiology study: personality disorders assessment in a prison population - Brinded, Philip M. J. (Criminal behaviour and mental health, 1999)
Three different measures of personality were used to assess the level of personality disorder in a prison population in Christchurch, New Zealand.Results using a traditional measure for antisocial personality disorder assessment (SCID II) are reported as well as other measures that do not rely on the categorical descriptions of personality disorder found in the DSM-IV. The other personality measures used were the "Four A's" and Temperament and Character Inventory (TCI), which have not previously been reported as being used in a prison population.The results are discussed with a particular focus on the relevance of the different types of personality disorder assessment to treatment planning and monitoring in a prison population. Copyright Ř 1999 Whurr Publishers Ltd